Cross Border Shopping from the Perspective of Domestic Tourists in Padang Besar, Perlis - Azmi, Azila; Ibrahim, Nurdin; Idris, Aida Khalida Mohamed; Ahmad, Zamri; Nor, Norfezah Md (European Journal of Economics and Business Studies, 2017)
Padang Besar is a border town in Malaysia and it is located in the northern part of Perlis, which shares a border with the province of Songkhla, Thailand. This border town is popular for shopping activities among Malaysian and Thai. Most visitors and tourists come during the weekends, sometimes up to thousands at one time. This research paper examines the motivations of cross border shoppers from the perspective of domestic tourists in Padang Besar, Perlis. The objective is to identify the consumer characteristics and analyze the relationship between market characteristics with cross border shopping. This study employs quantitative method and the data were collected using self-administered questionnaires. Statistical software was used to analyze the 375 returned questionnaires. The findings revealed that most of the domestic tourists came from the lower income group and most of them were day tripper. They tend to spend more on food and beverages, while their average spending is more than RM300. Moreover, market characteristics show strong positive relationship towards this shopping activity. The information gathered is beneficial for both neighbouring countries as the government can help to improve the shopping area by facilitating the development with related tourism infrastructure and amenities.
Keywords: shopping tourism, border town, consumer characteristics, market characteristics